Examining how global citizenship education is prefigured in the Scottish Curriculum for Excellence. (27th May 2022) - Anastasiadou, Elisavet; Moate, Josephine; Heikkinen, Hannu L.T.
ABSTRACT: This study uses the Aristotelian notion of phronesis as a critical lens for examining how global citizenship education is prefigured in the Scottish Curriculum for Excellence. Based on a content analysis of key curriculum documentation, the findings outline the way in which techne and episteme with their associated ways of knowing and acting dominate the curriculum. Nevertheless, the hints of phronesis indicate the potential for developing a more critical form of global citizenship education that prefigures praxis that wisely pursues that which is good for humankind and individual flourishing. This article contributes to the notion of 'planetary phronesis ' as a critical concept for the further development of global citizenship education.